Evaluating the Effects of Self-Care Practices on Dermatology Patients at Sharda University Hospital - Ashu Kumari; Chingngam P. Thangal; Soumi Das; Anee Rai; Alisha Saharawat; Divya Sharma (International Journal of Community Health Nursing And Practices, 2025)
Self-care is the ability of individuals, families and communities to promote their own health, prevent disease, maintain health, and to cope with illness with or without the support of a health or care worker." (WHO, 2020) This study looked into the demographics and self-care activities of patients who visited the Dermatology Department at Sharda Hospital. A descriptive survey design was used, with 50 participants aged 18-45 years selected using convenience sampling. Data was gathered using structured questionnaires that included demographic information, self-care behaviors, and open-ended comments about alternative therapies and health issues that affect skin health. The data found that the majority of participants were female (68%), aged 18-25 years (62%), and came from upper-middle-class socioeconomic situations (64%). Participants were somewhat engaged in self-care, with 80% scoring in the medium range on a self-care scale. Antibiotic use (30%) was the most commonly reported practice, while yoga (58% never practiced) and home remedies (36% never used) had low adoption rates. In addition, 84% of participants said they used drugs on a regular basis to control their skin health. The findings show a noticeable trend of younger persons and women seeking dermatological care, indicating increased awareness and concern about skin health in these groups. The study also emphasizes the importance of promoting holistic and sustainable self-care practices, such as yoga, balanced diets, and evidence-based home treatments. Limitations such as the limited sample size and reliance on self-reported data were highlighted, emphasizing the importance of future studies with bigger, more diverse populations and improved data gathering technologies.
Keywords: Dermatology; Self-Care Practices; Sharda Hospital; Yoga; antibiotics